2011
DOI: 10.1021/jf200859z
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Polymerization of Inulin-Type Fructans Differentially Affects Number of Lactic Acid Bacteria, Intestinal Immune Functions, and Immunoglobulin A Secretion in the Rat Cecum

Abstract: This study examined the role of degree of polymerization (DP) of inulin-fructans in modulating the interaction between lactic acid bacteria and IgA cecal secretion. Rats were fed a control diet or a diet containing one of the fructans with different DP. Consuming fructans increased the cecal IgA concentrations in the order DP4 > DP8 > DP16. Cecal lactobacilli counts were higher in DP4, DP8, and DP16, whereas bifidobacteria were higher in DP8, DP16, and DP23. Cecal IgA concentrations were correlated with cecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 41 publications
5
74
1
2
Order By: Relevance
“…Our results were in accordance with those of previous studies showing that dietary inulin with lower DP predominantly increased the proportion of Lactobacillus in healthy rodents (6,29,30). Conversely, Vos and others showed that Synergy 1 stimulated the growth of Lactobacillus more strongly than oligosaccharide or inulin in animal models (31).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results were in accordance with those of previous studies showing that dietary inulin with lower DP predominantly increased the proportion of Lactobacillus in healthy rodents (6,29,30). Conversely, Vos and others showed that Synergy 1 stimulated the growth of Lactobacillus more strongly than oligosaccharide or inulin in animal models (31).…”
Section: Discussionsupporting
confidence: 93%
“…The latter are subdivided into granulated inulin (GR; average DP of 10, ranging from 2 to 60), and high-performance inulin (HP; average DP of 24, ranging from 10 to 60) as well as Synergy 1, a specific 1 : 1 mixture of oligofructose and the HP-inulin. It has been established that both the rate and end products of gut microbial fermentation of fructans are affected profoundly by DP (5,6). Short-chain saccharides are likely to be fermented more rapidly than longer ones (7,8).…”
mentioning
confidence: 99%
“…FOSs (0.06% in the diet for 15 d) have been shown to increase the production of the immunoglobulin IgA in the cecum of rodents. Efficacy was dependent on FOS chain length, with shorter chain lengths resulting in higher cecal IgA concentrations (86). Shorter chain lengths resulted in higher viscosity and enhanced microbial fermentation (7,87).…”
Section: Impact Of Df On the Gut The Gatekeeper Of The Bodymentioning
confidence: 99%
“…Animal studies have shown that degree of polymerization of inulin-type fructans differentially affects metabolic status. 12,13 A randomized clinical trial to compare inulin and oligofructose-enriched inulin effect on glycemic indices and blood pressure in women with type 2 diabetes showed that inulin is effective than oligofructoseenriched inulin on food intake, glycemic indices and blood pressure in type 2 diabetes patients.…”
Section: Introductionmentioning
confidence: 99%